2022
DOI: 10.1007/s00395-022-00948-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calpain-1 activates NLRP3 inflammasome by cleaving ATP5A1 and inducing mitochondrial ROS in CVB3-induced myocarditis

Abstract: Treatment options for myocarditis are currently limited. Inhibition of calpains has been shown to prevent Coxsackievirus B3 (CVB3)-induced cardiac injuries, but the underlying mechanism of action of calpains has not been elucidated. We investigated whether NOD-, LRR-, and pyrin domain-containing 3 (NLRP3) inflammasome participated in CVB3-induced myocarditis, and investigated the effects of calpain-1 on CVB3-induced cardiac injury. NLRP3 inflammasome was activated in CVB3-infected hearts, evidenced by elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 63 publications
4
39
0
Order By: Relevance
“…Furthermore, hypoxia can trigger biochemical responses such as mitochondrial dysfunction and the release of reactive oxygen species (ROS) and cytokines, which increase the risk of myocardial injury. 34 This study also revealed that patients who received blood transfusions during surgery were also at a higher risk of postoperative myocardial injury. A study by Ronald et al demonstrated that blood transfusions may trigger immunosuppression and increase the incidence of postoperative infection in oncology patients.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, hypoxia can trigger biochemical responses such as mitochondrial dysfunction and the release of reactive oxygen species (ROS) and cytokines, which increase the risk of myocardial injury. 34 This study also revealed that patients who received blood transfusions during surgery were also at a higher risk of postoperative myocardial injury. A study by Ronald et al demonstrated that blood transfusions may trigger immunosuppression and increase the incidence of postoperative infection in oncology patients.…”
Section: Discussionmentioning
confidence: 69%
“…Mitochondrial fission alters the outer mitochondrial membrane permeability, resulting in Cyt c release into the cytoplasm, which activates the caspase pathway in a permanent manner and eventually causes apoptosis ( 83 ). Besides, mitochondrial damage also activates the NLRP3 inflammasome and causes cell death through ROS overproduction, MMP collapse, and other processes ( 72 , 84 , 85 ). Unbalanced mitochondrial dynamics, inclined to fission and fragmentation, were found in the models of myocardial injury and heart failure ( 86 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has confirmed that pyroptosis plays a critical role in various inflammation-related diseases such as myocarditis [ 59 ], neurodegeneration [ 60 ], or even cancer treatment [ 61 ]. However, whether pyroptosis contributes to wear particle-induced PPO warrants to be fully elucidated.…”
Section: Pyroptosis In Ppomentioning
confidence: 99%